Following up on smallholder farmers and supermarkets - Camilla I. M. Andersson; Christine G. Kiria; Matin Qaim; Elizaphan J. O. Rao (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2013)
In many developing countries, supermarkets are expanding rapidly. This also affects farmers' marketing options. Previous studies have analyzed welfare effects for smallholders with crosssection data. Here, we use panel data and a differencing approach to study supply chain dynamics and better account for unobserved heterogeneity in impact assessment. The analysis focuses on vegetable producers in Kenya. Participation in supermarket channels is associated with large income gains, which have further increased over time. However, many farmers are not able to enter supermarket channels, or they have dropped out due to various constraints. Specific support is needed to avoid widening income disparities.
Keywords: L24; O12; O13; Q12; Q13; Q18; 330; supermarkets; small farms; household income; panel data; Africa; Kenya